Structural characterization and species composition of mangrove vegetation in Lhokseumawe, Indonesia: Insight from multivariate analysis - Putri, Adinda Aulia; Erlangga, Erlangga; Syahrial, Syahrial; Ezraneti, Riri; Nufus, Hayatun; Leni, Yusyam; Rolin, Febrina (Journal of Marine Studies, 2024)
The structure of the plant community significantly influences the equilibrium of the surrounding environment, affecting the trophic interactions within its ecosystem. The investigation of mangrove vegetation in Cut Mamplam village was carried out in September 2021 to determine the condition and structural characteristics of the mangrove ecosystem by multivariate analysis. The mangrove vegetation in Cut Mamplam Village was sampled at three observation stations by establishing a transect parallel to the coast. Subsequently, the community structure was examined and assessed using cluster analysis and nonmetric multidimensional scaling using the PRIMER v7 software. The study findings indicate that the mangrove forest vegetation in Cut Mamplam Village consists of five species from three families. Avicennia alba, A. lanata, Bruguiera gymnorrhiza, Rhizophora mucronata and Sonneratia alba. The highest density of mangrove vegetation was observed in A. alba in all categories: trees (616.67 ind/ha), seedlings (833.33 ind/ha) and saplings (66666.67 ind/ha). Additionally, the highest important value index (IVI) was recorded in A. alba for all categories: trees (232.16%), seedlings (102.40%), and saplings (228.43%). A similarity of mangrove density between species was noted at 60%, resulting in the formation of two distinct groups. Regarding the basal area, the vegetation stands of A. alba and A. lanata exhibited the highest values (280.61 and 266.03 m2/ha, respectively). The similarity of basal area among the observed species was 20%, resulting in the formation of two distinct groups. Additionally, Station II, classified as having mature vegetation, demonstrated a maturity similarity of 80% between observation stations.